The influence of cement filler load on the radiopacity of various fibre posts ex vivo. (20th March 2014) - Goracci, C.; Juloski, J.; Schiavetti, R.; Mainieri, P.; Giovannetti, A.; Vichi, A.; Ferrari, M.
Abstract Aim To verify whether the filler load of luting agents influences the radiopacity of intraradicularly placed posts. Methodology Digital radiographs of the following posts were taken: RelyX Fiber Post (3M ESPE), GC Fiber Post (GC Corporation), DT Light Post Illusion (RTD), DT Light SL Post (RTD), Endo‐Composipost (RTD), FibreKleer Parallel Post (Jeneric Pentron Incorporated), FRC Postec (Ivoclar Vivadent), Parapost Taper Lux (Còltene/Whaledent AG), Radix Fiber Post (Dentsply Maillefer), EverStick Post (Stick Tech Ltd), Dentin Post X (Komet), Tech 21 X‐op (Isasan), ENA Post (Micerium). Post radiopacity was measured in millimetres of aluminium (mmAl) with reference to an aluminium step wedge. Two extracted contralateral premolars were root filled. After post space preparation, taking the midpoint of the post hole as a reference, each tooth was cut longitudinally into two halves in a mesiodistal direction. On each half, the exposed root dentine was ground flat to the deepest point of the post space, and an even layer of cement was placed and light‐cured. To obtain a clinically relevant layer of cement, the material thickness was reduced to 75 μm by grinding with wet abrasive paper. A cement formulation with 30 wt% of filler was tested in one premolar, whilst a formulation with 70 wt% of filler was utilized in the contralateral tooth. Posts were then placed between the two facing root halves of each premolar, and radiopacity was measured in mmAl. Data were analysed using t‐test for paired samples (P < 0.05). Results Radiopacity of posts ranged between 1.44 (ENA Post) and 5.78 mmAl (FibreKleer). In the presence of the more heavily filled cement, significantly higher values of post radiopacity were measured (P < 0.001). Conclusion The radiopacity of the luting agent contributed to the overall post radiovisibility within the root. Even when the cement with lower filler content was used in combination with the least radiodense dowels, the post was detectable within the root.